Effects of yogurt dietary supplementation on the intestinal ecosystem of a population of Emperor tamarins (Saguinus imperator) - Pinna, Carlo; Nannoni, Eleonora; Rigoni, Giulia; Grandi, Monica; Vecchiato, Carla Giuditta; Spiezio, Caterina; Sandri, Camillo; Biagi, Giacomo (Progress in Nutrition, 2015)
Providing hidden food is a method of nutritional and environmental enrichment for captive animals and yogurt is sometimes used with this purpose for non-human primates. Objective of the present study was to evaluate the effect of feeding fresh yogurt on the intestinal ecosystem of Emperor tamarins (Saguinus imperator). A population of nine adult/juvenile emperor tamarins received during the whole trial a diet mainly consisting of different fruits. During the first 30 d, the diet did not contain any yogurt; during the following 28 d, every two days, a total of 300 g of fresh fruit yogurt was provided to the animals. A fresh fecal sample was collected from each animal the day before administration of yogurt started (Day 0) and again after 21 and 28 days for chemical and bacterial determinations. Throughout the study, all tamarins remained in good health and no clinical signs of intestinal discomfort were observed. During yogurt supplementation, fecal pH, moisture and ammonia resulted unchanged respect to the beginning of the study. Similarly, fecal volatile fatty acids were not affected by the yogurt intake. On the contrary, fecal spermine concentration resulted significantly decreased at Day 28 respect to Day 0 (4.4 vs. 30.1 nmol/g of feces; P < 0.05). Furthermore, the consumption of yogurt resulted in reduced fecal concentrations of coliforms, enterococci and lactobacilli on Rogosa Agar (respectively, -1.9, -1.5 and -2.8 log CFU/g of feces; P < 0.05). Results from the present study showed that emperor tamarins can tolerate high amounts of yogurt in their diet without showing any signs of lactose malabsorption (for example, soft feces or diarrhea). On the other hand, yogurt ingestion failed to exert any major influence on the animals intestinal microbiota.